Pemanfaatan Berbagai Jenis Gulma sebagai Bahan Biosaka untuk Meningkatkan Produksi Bawang Merah (Allium ascolanicum L.): Utilization of Various Weeds as Biosaka Materials to Increase the Production of Shallots (Allium ascolanicum L.) - Hamdan Drian Adiwijaya; Lusiana; Ika Cartika (Politeknik Pertanian Bogor, 2023)
Sustainable agricultural policies encourage agricultural innovations such as the use of bio saccharides as elicitors in plants. Biosaka contains chemical compounds that trigger a positive response in plants. Shallots are a superior commodity whose cultivation practices often do not pay attention to the negative impacts on the environment. Using biosaka as an alternative can support more environmentally friendly shallot farming. This research aims to identify the effect of using a biosaka elicitor on the growth and production of shallots. The research was carried out from July to September in Kab. Subang, West Java with an altitude of 10 m above sea level. The biosaka elicitor treatment was carried out using 3 treatment formulas, namely A: formula 1 (babadotan, kitolod, anting-anting, maman lanang, and pasang bumi), B: formula 2 (jelantir, sembung, patikan kebo, meniran, and sembung rambat), C: formula 3 (babadotan, anting-anting, sembung, jelantir and meniran), D: control (without elicitor), treatment was repeated 6 times. The results of the research show that all weed-based bio saccharide elicitor formulations can increase plant height, number of leaves, and weight of onion bulbs. Selection of appropriate elicitors with appropriate cultivation techniques can produce optimization plant product.